Influence of the vertically arranged front injector system on the performance and operational stability of the short jet pump - Ma, Xiaogang; Yang, Jun; Dai, Tingting; Wang, Jun; Tang, Lei; Yang, Yang (Frontiers in Energy Research, 2024)
As the core component of a water conservancy sprinkler irrigation system, the self-priming jet pump is required not only to meet performance criteria for self-priming but also to align with the growing trend toward compactness in sprinkler irrigation systems. This paper takes the short compact self-priming jet pump as the research object whose injector is perpendicular to the main flow direction of the impeller inlet in order to reduce the volume of the jet pump and adopts the method of numerical simulation combined with experimental validation to study the effect of vertical arrangement of the injector on the hydraulic characteristics and operational instability of the self-priming jet pump. The results show that compared with the traditional hydraulic structure, the front injector leads to a significant reduction in the applicable flow range of the short jet pump. The hydraulic efficiency of the jet pump is notably inferior to that of traditional pumps across various flow conditions. This discrepancy arises from the eccentric rotation induced by the front-mounted injector, leading to pronounced circumferential asymmetry in the media flow within the individual impeller channels. Consequently, this asymmetry contributes to increased hydraulic losses in the flow channel. At the same time, the smaller overflow area within the injector enhances the turbulent flow characteristics of the medium, leading to increased instability of the subsequent flow field. This induces the generation of unwieldy low-frequency pressure pulsation signals within the flow channel, which are more readily propagated throughout the sprinkler system. In the practical application of short jet pumps, the circumferentially asymmetric distribution of the media flow in the impeller channel may result in the eccentric rotation of the rotor, thereby diminishing the service life of the pump. Furthermore, the complicated low-frequency signals will induce low-frequency vibration of the hydraulic sprinkler system, reducing the operational stability of the sprinkler system.